The Influence of Profitability Ratio To Share Price On Telecommunication Company Listed In Indonesia Stock Exchange Period 2013-2015 - Muktamaria, Muktamaria; Sukoco, Agus (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2018)
Influence is a power that can shape or change something else. So in this study the authors examine about how much power that is or caused by the analysis of Profitability ratios to stock prices. The purpose of this research is to know the profitability ratios of telecommunication companies listed in Indonesia Stock Exchange period 2013-2015, to know the stock price of telecommunication company listed in Indonesia Stock Exchange period 2013-2015, and to know how influence profitability ratio to stock price of telecommunication company . This research is conducted on telecommunication companies listed in Indonesia Stock Exchange period 2013-2015 that is, PT. XL Axiata Tbk, PT. Smartfren Telecom Tbk, PT. Indosat Tbk, PT. Telekomunikasi Indonesia Tbk, PT. Tower Bersama Infrastruktur Tbk, PT. Solusi Tunas Pratama Tbk, PT. Inti Bangun Sejahtera Tbk. The data used are secondary data in the form of financial statements.